Climate Change 2007 - "Solomon,Susan (ed.)" (New York, 2007)
The Climate Change 2007 volumes of the Fourth Assessment Report of the Intergovernmental Panel on Climate Change (IPCC) provide the most comprehensive and balanced assessment of climate change available. This IPCC Working Group I report brings us completely up-to-date on the full range of scientific aspects of climate change. Written by the world's leading experts, the IPCC volumes will again prove to be invaluable for researchers, students, and policymakers, and will form the standard reference works for policy decisions for government and industry worldwide.
Keywords: Environment